CHARACTERIZATION OF NI–CO COATINGS ELECTRODEPOSITED FROM ELECTROLYTES WITH DIFFERENT CO CONCENTRATIONS - HERZALLAH, O.; BEN TEMAM, H. (Courrier du Savoir; Vol. 23 (2017): COURRIER DU SAVOIR (JUIN), 2017)
In this work, Ni-Co composite coatings with different Co contents were prepared by electrodeposition from modified Watts bath containing different Co+2 amounts. The effects of Co contents on the composition, crystal structure, surface morphology, and corrosion resistance of the Ni-Co composite coatings were investigated. Morphology and microstructure were studied by scanning electron microscope and XRD analysis. Pebbly, spherical granular and acicular morphology were illustrated with SEM micrographs and combination of fcc and hcp structure were characterized by XRD patterns which depended strongly on cobalt content in the deposit. The electrochemical properties of Ni- Co alloy coatings were evaluated in 3.5 % NaCl solution by means of potentiodynamic polarization technique. A better corrosion resistance was obtained for pure nickel deposit.